Облік розрахунків з постачальниками в умовах санкційних обмежень та міжнародного фінансового комплаєнсу - Краєвський, Володимир Миколайович; Колісник, Олена Пилипівна; Мегедь, Тарас Григорович (Видавничий дім «Гельветика», 2025)
У статті досліджено теоретико-методологічні засади обліку розрахунків з постачальниками в умовах санкційних обмежень та міжнародного фінансового комплаєнсу. Розкрито концептуальні основи побудови облікових систем у транснаціональному контексті, враховуючи виклики фінансово-правової турбулентності та санкційної політики. Особливу увагу приділено аналізу впливу глобальних стандартів фінансової звітності (IFRS) на облікові процеси у режимі санкцій. Досліджено інституційну природу санкцій та їх роль у регулюванні міжнародної торгівлі, а також облік операцій з нерезидентами в умовах посилених санкційних ризиків. Розглянуто корпоративні стратегії подолання санкційних бар’єрів у фінансових операціях. Проаналізовано генезу та еволюцію концепції міжнародного фінансового комплаєнсу, інтеграцію комплаєнс-процедур у систему корпоративного управління фінансами та роль автоматизованих систем контролю (AML, KYC) у забезпеченні прозорості розрахункових операцій. Окремо наведено аналітику кейсів порушень фінансового комплаєнсу та їх облікове трактування. Отримані результати дозволяють сформувати стратегічні підходи до управління роз рахунками з постачальниками у складних умовах глобального економічного середовища.

Modern transnational companies and enterprises operate in an environment characterized by a high level of financial and legal turbulence and increased restrictions on sanctions. This necessitates a rethinking of methods for accounting for payments to suppliers, in the context of international financial compliance. In the context of globalization of economic processes, ensuring transparency, reliability and efficiency of financial transactions is of particular importance, which requires the integration of new approaches and compliance with international accounting standards. The research issues are related to the insufficient development of theoretical and methodological foundations of accounting under sanctions and the need for effective integration of compliance procedures into the financial activities of enterprises. The purpose of the article is to substantiate the theoretical and methodological principles of accounting for payments to suppliers in a transnational context, considering sanctions restrictions and requirements of international financial compliance. The research is aimed at identifying key problems and challenges, developing methodological approaches to organizing accounting processes in modern conditions, as well as determining strategic directions for overcoming sanctions barriers in financial transactions. To achieve the goal, a complex of scientific methods was used, including systemic and comparative analysis to study international practices of financial compliance and accounting standards; induction and deduction to generalize theoretical provisions. The study identified the conceptual foundations of accounting for settlement transactions in a transnational context, focusing on the impact of financial and legal turbulence. A methodology for building accounting systems considering sanctions and compliance requirements was developed, which includes the adaptation of global financial reporting standards (IFRS) to the conditions of sanctions policy. The institutional nature of sanctions and their multidimensional impact on accounting processes, on the accounting of receivables and payables, were separately analyzed.
Accounting for payments with suppliers under sanctions and international financial compliance
Keywords: облік розрахунків; зобов’язання; санкційні обмеження; фінансовий комплаєнс; міжнародна торгівля; IFRS; accounting; liabilities; sanctions; financial compliance; international trade; IFRS